Prostorski vidiki načrtovanja logističnih središč - Zavrtanik, Jure (Urbani izziv, 2009)
Spatial planning of logistics centres follows specific spatial and infrastructural requirements, conditioned by desired traffic flux and scope. Spatial and environmental limitations of the usual freight handling sites are forcing logistical activities to search for areas that can ensure undisturbed expansion and practically unlimited traffic flows. The consequence of this trend is suburbanisation coupled with all the spatial and environmental effects. Within this framework, set against the awareness of the uniqueness ofany particular site, the article points out the significance of a comprehensive and timely spatial and environmental planning of logistical centres. Therefore clear spatial objectives, transparent analytical starting blocks and adequate planning regulation prove to be the imperative in the spatial planning of logistical centres and formulation of the spatial concept. Simultaneously, and with respect to the complexity of spatial developments, the significance of territorial cohesion is emphasised, which ismanifested as territorial identity, territorial quality and territorial efficiency.
Keywords: gospodarske dejavnosti; logistika; Lower Sava Valley; Posavje; promet; prostorsko planiranje; spatial planning